Systematics of New World Curtonotum Macquart (Diptera: Curtonotidae) - Klymko, John; Marshall, Stephen A. (Zootaxa, 2011)
The New World species of the curtonotid genus Curtonotum Macquart are reviewed, and all species outside the vulpinum and murinum species complexes (as defined below) are revised. Descriptions and illustrations are provided for 24 species, including 13 newly described species: C. adusticrus sp. n., C. atlanticum sp. n., C. bivittatum sp. n., C. brunneum sp. n., C. curtispinum sp. n., C. desperatum sp. n., C. papillatum sp. n., C. gracile sp. n., C. hunkingi sp. n., C. flavisetum sp. n., C. floridense sp. n., C. nigrum sp. n., and C. scambum sp. n. Curtonotum nigripalpe Hendel is proposed as a new junior synonym of C. hendelianum (Enderlein). A key to these New World species is presented and the phylogenetic relationships between them are discussed. Lectotypes are designated for C. tumidum Enderlein, C. bathmedum Hendel, C. taeniatum Hendel, C. trypetipenne Hendel, C. impunctatum Hendel, 1913, nec impunctatum Hendel, 1932 and C. apicale Hendel. Curtonotum perplexum nom. n., is given as the replacement name for C. impunctatum Hendel, 1932 nec impunctatum Hendel, 1913. Two species complexes are left untreated at the species level (the C. murinum species complex, including C. murinum Hendel, C. coriaceum Hendel, C. perplexum nom. n., and C. decumanum Bezzi; and the C. vulpinum species complex including C. vulpinum Hendel and C. fumipenne Hendel). Both complexes are included in the phylogenetic analysis and key.